Discrepancy in the suppressive function of regulatory T cells in allergic asthmatic vs. allergic rhinitis subjects upon low-dose allergen challenges - Klein, Martin; Plante, Sophie; Boulay, Marie-Ève; Boulet, Louis-Philippe; Chakir, Jamila (Frontiers in Allergy, 2023)
Background: Regulatory T cells (Tregs) contribute to the maintenance of immunological tolerance. There is evidence for impaired function of these cells in asthma and allergy. In this study, we evaluated and compared Tregs function in allergic asthmatic and allergic non asthmatic participants, before and after low dose allergen challenge. Methods: Three groups of subjects were recruited for a baseline evaluation: healthy controls without allergy or asthma, allergic asthmatic and allergic non-asthmatic subjects. All underwent expiratory flow measurements, sputum induction, and blood sampling. In addition, both groups of allergic subjects underwent low dose allergen challenges. Tregs were isolated from whole blood using CD4 + CD25 high and CD127 low staining. Suppression test was measured by flow cytometry. IL-10, IFN-, IgG4, IgA and TGF- were measured by ELISA and sputum Foxp3 was evaluated by qRT-PCR. Results: Suppressive function of Tregs in healthy controls was significantly higher than in allergic asthmatic or allergic non-asthmatic subjects. Repeated exposure to low doses of allergen increased the suppressor function of Treg in allergic non-asthmatic subjects but decreased it in allergic asthmatic subjects. Foxp3 gene expression was increased in induced sputum in allergic non asthmatic subjects whereas it did not change in asthmatic subjects. Serum IL-10 decreased in allergic asthmatic subjects after allergen challenge but not in allergic non-asthmatic subjects.IFN- increased upon allergen challenge in allergic non asthmatic subjects. IgG4 was higher in allergic non-asthmatic compared to allergic asthmatic subjects. Conclusions: Low dose allergen challenges stimulate the suppressor function of Tregs in non-asthmatic allergic subjects but not in allergic asthmatic subjects.